2015
DOI: 10.1038/tp.2015.1
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal cortex markers of suicidal vulnerability in mood disorders: a model-based structural neuroimaging study with a translational perspective

Abstract: The vulnerability to suicidal behavior has been modeled in deficits in both valuation and cognitive control processes, mediated by ventral and dorsal prefrontal cortices. To uncover potential markers of suicidality based on this model, we measured several brain morphometric parameters using 1.5T magnetic resonance imaging in a large sample and in a specifically designed study. We then tested their classificatory properties. Three groups were compared: euthymic suicide attempters with a past history of mood dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 48 publications
4
67
1
2
Order By: Relevance
“…Decreased brain volumes in the prefrontal cortex of suicidal patients also have been described (Ding et al, 2015), possibly reflecting neuroplasticity impairment. Pro-inflammatory cytokines are associated with decreased neurogenesis and induce reductions in BDNF expression, mRNA and protein levels (Calabrese et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Decreased brain volumes in the prefrontal cortex of suicidal patients also have been described (Ding et al, 2015), possibly reflecting neuroplasticity impairment. Pro-inflammatory cytokines are associated with decreased neurogenesis and induce reductions in BDNF expression, mRNA and protein levels (Calabrese et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A magnetic resonance imaging (MRI) study found that depressed patients at high suicide risk had a significantly thinner cortex in the left dorsolateral and ventrolateral prefrontal regions than those at a lower suicide risk [7]. A recent MRI study indicated that suicide attempters (SAs) with a past history of mood disorders have reduced activity in the left ventrolateral prefrontal cortices compared with healthy controls (HCs) and with patient controls with a past history of mood disorders but not of suicidal behavior [8]. Furthermore, functional MRI (fMRI) studies have shown that SAs can be distinguished from non-attempters (NAs) by specific frontal cortex activation patterns in response to angry and happy versus neutral faces [9] and by decreased activation in the medial prefrontal cortex while reading autobiographical accounts of recent suicide attempts compared with while reading neutral scripts [10].…”
Section: Introductionmentioning
confidence: 99%
“…The brain’s inability to respond properly to environmental stimuli due to impaired structural and neural plasticity has been well-established to cause suicide pathogenicity (Dwivedi, 2009, 2010; Furczyk et al, 2013). Recent neuroimaging identification of orbitofrontal and dorsolateral prefrontal cortex based structural abnormalities in suicide victims further reinforces the importance of impaired neuronal plasticity (Ding et al, 2015; van Heeringen et al, 2011). An overwhelming concern and ever-increasing need to better apprehend this compromised structural and functional plasticity, eventually unfolded the role of brain-derived neurotrophic factor (BDNF) and its cognate receptor molecule tropomycin receptor kinase B (TRKB) in suicide neurobiology (Dwivedi, 2009, 2010; Dwivedi et al, 2003; Lee and Kim, 2010; Pandey et al, 2008).…”
Section: Influence Of Dna Methylation Based (5mc) Epigenetic Modifmentioning
confidence: 83%